(untitled) (Bangladesh Veterinarian, 2010)
The prevalence of colibacillosis in layer chickens was studied from May to September 2007. Sixty five cloacal swabs from apparently healthy birds and 55 swabs of liver (n=15), lung (n=15) and intestine (n=25) from 30 dead birds were collected in sterile nutrient broth, with histopathological samples. Bacteria were isolated and identified. Tissue samples were studied under light microscope. Escherichia coli (E. coli) was isolated from 83% of cloacal swabs of apparently healthy chickens and 87% of samples from dead birds. Affected birds had cloudy thickened air sacs, pericarditis, congestion in the liver, lung and spleen. On histopathological examination focal necrosis in liver and infiltration of heterophils, lymphocytes and macrophages in liver and lung was found. Thickening of pericardium was found due to infiltration of reticulo endothelial (RE) cells. In duodenum, severe infiltration of leukocytes mainly heterophils, lymphocytes and macrophages was found in the sub-mucosa. DOI: 10.3329/bvet.v25i1.4614 Bangl. vet. 2008. Vol. 25, No. 1, 17-24